Melting relations of undersaturated alkaline Rocks from South Greenland. - Piotrowski, J. M.; Edgar, A. D. (Meddelelser om Grønland, 1970)
Sixteen volcanic and plutonic undersaturated alkaline rocks of diverse compositions from Greenland, Africa and Canada have been examined petrographically and their melting relations determined at 1 atmosphere pressure in air; 4 samples have been melted in an argon (non-oxidizing) environment and 6 samples at water vapour pressures up to 2070 bars. At 1 atmosphere pressure, liquidus temperatures range from 1120° to 1230° C; in the non-oxidizing atmosphere, liquidus temperatures are similar but iron-bearing minerals remain in the same oxidation state as in the unheated rock. Water vapour pressures lower liquidus temperatures by as much as 300° C with the initial 1000 bars pressure being most effective. For the majority of samples the sequence of crystallization is nepheline, feldspar and pyroxene at 1 atmosphere pressure. Argon atmosphere and water vapour pressure alters this sequence for some rocks. There is a direct relationship between the melting intervals and chemistry of the rocks. Rocks showing agpaitic trends (USSING, 1912) and high volatile contents have much longer melting intervals. A comparison of the melting data of the rocks studied with data from pertinent synthetic systems indicates high liquidus temperatures for many of these rocks when compared to synthetic systems at 1 atmosphere, but good agreement was found between the hydrothermally melted rocks and the synthetic systems at equivalent pressures. For some of the specimens, tie-lines between coexisting nephelines and feldspars have been determined for the unheated rocks and for rocks heated to 975° C. When plotted on the system KaA-SiO4-KAlSiO4-SiO2 , the slopes of the tie-lines compare favourably with those suggested by TILLEY (1958) for rocks from plutonic and volcanic environments. Relationships between Jiquidus temperatures, chemistry and petrography are discussed.